BAHASA BETAWI DAN GAYA BAHASA REPETISI DALAM CERAMAH USTAD YUSUF MANSUR PROGRAM WISATA HATI DI ANTV - Ninit Alfianika (Jurnal Gramatika, 2015)
The purpose of this study was (1) to describe the use of Betawi in ceramaha Ustad Yusuf Mansur and (2) describe the use of force in the lecture repetisis language Ustad Yusuf Mansur. Data collected through three stages, (1) listening and video mentransipkan Ustad Yusuf Mansur in Islamic lecture entitled Riadho 40 Days, Charity, and Night Prayer taken from youtobe, (2) identify and record the repeated utterances into research data, and (3) an inventory of words related to the Betawi language and stylistic repetition by using the format of the data inventory. Analyzing data descriptively. Based on the results of the study concluded the following, first, from the results of the study, the authors found 45 speech that had the Betawi. 45 speech that I have found there are three lecture titles, namely (1) Riadho 40 days, (2) Charity, and (3) Prayer Night. In a lecture titled 40 Days Riadho found 23 utterances. In a lecture titled Alms found 14 utterances. In a lecture titled Evening Prayer found 8 speech. Second, the language style reps were found in three lectures Ustad Yusuf Mansur is, epizeuksis, anaphora, and anadiplosis. Of the three types of stylistic repetition found there are 33 utterances that contain stylistic repetition. Stylistic repetition epizeuksis types totaled 22 utterances. Stylistic repetition consists of 3 types of anaphora speech. Stylistic repetition anadiplosis are 8 types of utterances. Thus, from the results of the research can be authors conclude Betawi and stylistic hallmark reps merupan Ustad Yusuf Mansur in rhetoric.